Emergency Department Visits Before, After and During Integrated Home Care: A Time Series Analyses in Italy - Sara Campagna; Alessio Conti; Valerio Dimonte; Paola Berchialla; Alberto Borraccino; Maria Michela Gianino (Kerman University of Medical Sciences, 2022)
Background  Integrated home care (IHC) is one strategy to provide care to people with multiple chronic conditions, and it contributes to the reduction of unnecessary emergency department (ED) use, but there are conflicting results on its effectiveness. In this study, we assessed the frequency and characteristics of ED visits occurring before, during, and after IHC in a large cohort of IHC patients enrolled over 6 years.Methods  The analysis included 39 822 IHC patients identified in Italian administrative databases. Patients were grouped in tertiles according to IHC duration (short, intermediate, and long) and the number of ED visits during IHC was compared to that the 12 months before IHC enrolment and in the 12 months after IHC discharge across IHC duration groups.Results  We observed a reduction in ED visits during IHC. IHC was significantly associated with a reduction in ED visits in the long and short IHC duration groups. A non-significant reduction in ED visits was observed in the intermediate IHC duration group. A 90% reduction in ED visits during IHC and a 45% reduction after IHC was observed in the short IHC duration group. Corresponding reductions were 17% and 64% during and after IHC, respectively, in the long IHC duration group.Conclusion  IHC was effective in reducing ED visits, but expansion of IHC to include additional necessary services could further reduce ED visits. Investment in the creation of a structured, effective network of engaged professionals (including community care services and hospitals) is crucial to achieving this.